Electrolytic coloring method for corrosion-resistant cobalt-molybdenum-chromium alloy
Patent Information
- Application Number
- CN202611210402.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的在于提供一种用于耐蚀钴钼铬合金的电解着色显示方法,解决现有技术中常规蚀刻方法对基体相与Laves相显示衬度不足、无法利用灰度法自动测定Laves相占比,以及Murakami试剂毒性大、不环保的技术问题
[0030]本发明通过含可溶性钼酸盐的碱性水溶液电解着色,使Laves相呈棕色、基体相呈亮白色,两相在金相显微镜下形成鲜明的颜色衬度,克服了王水腐蚀法和草酸电解腐蚀法衬度不足的缺陷,可直接利用金相图像分析软件的灰度提取法进行Laves相比例的自动识别和定量测定;同时,本发明所用试剂为碱性物质和可溶性钼酸盐,均为金相实验室常用化学品,不涉及铁氰化钾等剧毒物质,操作过程中无有毒气体释放,废液处理简便,对环境友好,克服了Murakami试剂腐蚀法使用受限的缺陷;此外,本发明在室温条件下即可完成电解着色,无需加热,设备要求低,操作步骤简单、耗时短,且试剂配制方便、重现性好,便于在金相检验领域推广应用。
Smart Images

Figure CN122882175A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallographic analysis technology, and more specifically, to an electrolytic coloring display method for corrosion-resistant cobalt-molybdenum-chromium alloys. Background Technology
[0002] Cobalt-molybdenum-chromium (Co-Mo-Cr) alloys are widely used in biomedicine and high-end industrial manufacturing due to their excellent corrosion resistance, wear resistance, and good biocompatibility. In these applications, the microstructure of the alloy, especially the morphology, distribution, and content of the matrix phase (γ phase) and precipitated phases (such as the Laves phase), directly determines the mechanical properties and service life of the material. Therefore, in metallographic analysis, clearly and accurately displaying and distinguishing these phase structures is crucial for material quality control and performance evaluation. Currently, commonly used etching methods for cobalt-based alloy metallographic structures include aqua regia etching, Murakami reagent etching, and oxalic acid electrolytic etching. However, these methods not only fail to provide sufficient phase contrast, making it impossible to directly use metallographic analysis software for grayscale extraction and quantitative determination; but some methods also easily generate highly toxic products, which is detrimental to operator health and environmental protection, greatly limiting their application scope.
[0003] Patent application number 202010342282.9 discloses an etchant and etching method for displaying the metallographic structure of cobalt-chromium-molybdenum alloys. It uses strong alkalis and oxidants to effectively reduce etching time and improve etching effect, but it does not solve the technical problems of insufficient color contrast between the matrix phase and the Laves phase, making automated quantitative analysis difficult. Patent application number 201910143597.8 discloses an electrolytic etching method for precipitating strengthening phases in cobalt-based alloys, which uses an acidic electrolyte of concentrated nitric acid, acetic acid, and water to etch the matrix to expose the γ′ strengthening phase. However, this method can only create morphological contrast and cannot specifically color the molybdenum-rich Laves phase.
[0004] Therefore, there is an urgent need to develop a metallographic corrosion method that is both safe and environmentally friendly, and can significantly enhance the contrast between the matrix phase and the Laves phase in cobalt-molybdenum-chromium alloys through specific coloring, thereby facilitating accurate and automated quantitative analysis. Summary of the Invention
[0005] The purpose of this invention is to provide an electrolytic coloring display method for corrosion-resistant cobalt-molybdenum-chromium alloys, which solves the technical problems of insufficient contrast between the matrix phase and the Laves phase in conventional etching methods, the inability to automatically determine the proportion of the Laves phase using grayscale methods, and the high toxicity and environmental unfriendliness of Murakami reagent.
[0006] To achieve the above objectives, the present invention provides an electrolytic coloring display method for corrosion-resistant cobalt-molybdenum-chromium alloys. The method uses an alkaline aqueous solution containing soluble molybdate as the electrolytic coloring reagent, and uses a cobalt-molybdenum-chromium alloy sample as the anode for electrolytic treatment, so that a molybdenum oxide coloring film is formed on the surface of the Laves phase, thereby making the matrix phase and the Laves phase appear in different colors under a metallographic microscope.
[0007] Further, the method includes the following steps: preparing an aqueous solution containing an alkaline substance and a soluble molybdate as an electrolytic coloring reagent; immersing the prepared cobalt-molybdenum-chromium alloy sample as the anode and an inert conductive material as the cathode in the electrolytic coloring reagent and passing direct current through it for electrolytic coloring.
[0008] This invention achieves selective coloring based on the principle of electrolytic anodizing. Under alkaline electrolysis conditions, the cobalt-molybdenum-chromium alloy sample serves as the anode. The matrix phase (γ-solution) undergoes anodic dissolution, altering the surface microstructure and resulting in enhanced light reflection under a metallographic microscope, exhibiting a bright white color. Meanwhile, the Laves phase, enriched in Mo and Si, exhibits superior corrosion resistance compared to the matrix and acts as a micro-cathode during electrolysis, driving the MoO4 in the solution. 2- A reduction reaction occurs: MoO4 2- +2e - →Mo 4+ Brown MoO2 is deposited on the surface of the Laves phase. As a result, the Laves phase is brown and the matrix phase is bright white, creating a striking color contrast between the two phases.
[0009] The role of the alkaline substances is to provide an alkaline electrolytic environment, enabling anodic dissolution of the matrix phase, and simultaneously providing suitable pH conditions for the reduction reaction of molybdate. The role of soluble molybdate is to provide MoO4. 2- A brown molybdenum oxide coloring film is generated on the surface of the Laves phase by reduction.
[0010] Furthermore, the electrolytic coloring treatment makes the Laves phase appear brown and the matrix phase appear bright white, creating a color contrast between the two under a metallographic microscope.
[0011] Furthermore, the preparation method of the electrolytic coloring reagent is as follows: add 5g~15g of alkaline substance and 5g~10g of soluble molybdate to every 100mL of aqueous solution.
[0012] Furthermore, the soluble molybdate is one or more of sodium molybdate, potassium molybdate, or ammonium molybdate, the alkaline substance is one or two of sodium hydroxide and potassium hydroxide, and the inert conductive material is one or more of stainless steel, platinum, and graphite.
[0013] It should be noted that in this invention, a strongly alkaline electrolyte (pH > 12) is used for electrolysis.
[0014] Furthermore, this includes the following steps:
[0015] (1) Sample preparation: Grind and polish the test surface of the cobalt-molybdenum-chromium alloy sample to a mirror finish;
[0016] (2) Preparation of electrolytic reagent: Dissolve sodium hydroxide and sodium molybdate in water and stir evenly to obtain the electrolytic coloring reagent;
[0017] (3) Electrolytic coloring: Using the prepared cobalt-molybdenum-chromium alloy sample as the anode and stainless steel as the cathode, the test surface of the cobalt-molybdenum-chromium alloy sample is immersed in the electrolytic coloring reagent and electrolyzed by passing a direct current through it.
[0018] (4) Cleaning: Take out the sample, rinse the test surface with deionized water and anhydrous ethanol, and air dry it for metallographic observation.
[0019] Furthermore, in step (3), the distance between the cobalt-molybdenum-chromium alloy sample and the stainless steel is 1cm to 5cm.
[0020] Furthermore, in step (3), the electrolysis current is 0.5A~1.5A, the voltage is 3V~10V, and the electrolysis time is 15s~100s.
[0021] In this invention, current, voltage, electrode spacing, and electrolysis time have a synergistic effect on the coloring effect, and the preferred range of each parameter is determined based on the following considerations:
[0022] Current directly affects the driving force of electrochemical reactions. When the current is too low (less than 0.5A), the driving force of the reaction is insufficient, the coloring is slow and uneven, and the oxide coloring film of sufficient thickness cannot be formed on the surface of the Laves phase, resulting in a light color and insignificant contrast. When the current is too high (greater than 1.5A), the reaction is violent, which may cause the film layer on the surface of the Laves phase to peel off or the substrate to be over-corroded, thereby damaging the morphology and adversely affecting the coloring effect.
[0023] The voltage automatically fluctuates between 3V and 10V depending on the current. When the voltage is too low (less than 3V), the electric field strength is insufficient to effectively drive the electrode reaction, and the coloring film formation rate is too slow; when the voltage is too high (greater than 10V), it may lead to an aggravation of the oxygen evolution side reaction, affecting the quality of the coloring film and the surface uniformity.
[0024] The distance between the sample and the cathode affects the electric field distribution and ion migration path in the electrolyte. If the distance is too small (less than 1 cm), the local current density will be too high, which can easily cause uneven coloring or even local over-corrosion on the sample surface. If the distance is too large (greater than 5 cm), the resistance will increase, the electric field distribution will tend to be dispersed, the voltage will increase under the same current, the electrolysis efficiency will decrease, and the temperature may rise due to the resistive heating effect of the solution, which may affect the coloring stability.
[0025] Electrolysis time is a key parameter for controlling the thickness of the colored film. If the time is too short (less than 15s), the oxide film has not been fully formed, and the Laves phase surface only shows a weak color or even no color, making it impossible to effectively distinguish. If the time is too long (greater than 100s), the film layer continues to thicken, which may result in film peeling or the color being too dark to cover up the tissue details, thus affecting the accuracy of grayscale determination.
[0026] In this invention, electrolysis is preferably carried out at room temperature.
[0027] Furthermore, in step (1), 80-mesh, 240-mesh, 400-mesh, 800-mesh, and 1200-mesh wet sandpaper are used for polishing in sequence, and a soft cloth is used in conjunction with a diamond polishing agent with a particle size of 0.5μm for polishing.
[0028] Furthermore, the cobalt-molybdenum-chromium alloy sample is Tribaloy T-400.
[0029] Compared with existing technologies, the electrolytic coloring display method for corrosion-resistant cobalt-molybdenum-chromium alloys described in this invention has the following advantages:
[0030] This invention utilizes electrolytic coloring with an alkaline aqueous solution containing soluble molybdate to produce a brown Laves phase and a bright white matrix phase. The two phases exhibit a distinct color contrast under a metallographic microscope, overcoming the insufficient contrast of aqua regia and oxalic acid electrolytic etching methods. The Laves phase ratio can be automatically identified and quantitatively determined directly using grayscale extraction in metallographic image analysis software. Furthermore, the reagents used in this invention are alkaline substances and soluble molybdates, both commonly used chemicals in metallographic laboratories, and do not involve highly toxic substances such as potassium ferricyanide. No toxic gases are released during the operation, waste liquid treatment is simple, and it is environmentally friendly, overcoming the limitations of the Murakami reagent etching method. In addition, this invention can complete electrolytic coloring at room temperature without heating, requiring minimal equipment, with simple and quick operation steps. The reagents are easy to prepare and have good reproducibility, facilitating its widespread application in the field of metallographic testing. Attached Figure Description
[0031] Figure 1 The image shows the metallographic structure of the Tribaloy T400 alloy obtained in Example 1 of this invention.
[0032] Figure 2 This is a metallographic photograph of the Tribaloy T400 alloy obtained in Comparative Example 1 of this invention.
[0033] Figure 3 This is a metallographic photograph of the Tribaloy T400 alloy obtained in Comparative Example 2 of this invention.
[0034] Figure 4A metallographic photograph of the Tribaloy T400 alloy obtained in Comparative Example 3 of this invention;
[0035] Figure 5 This is a metallographic photograph of the Tribaloy T400 alloy obtained in Comparative Example 4 of this invention. Detailed Implementation
[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the described embodiments are only some, not all, of the embodiments of this invention. The specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.
[0037] Cobalt-molybdenum-chromium alloys, with Kennametal's Tribaloy T-400 cobalt-based wear-resistant alloy as a typical example, have the main components Co-Mo28-Cr8.5-Si2.6 and are commonly used for wear-resistant components in high-temperature (800~1000℃) and corrosive environments, such as valve seats and sealing rings. The as-cast microstructure of this alloy is generally cobalt-based γ-solution plus a Mo- and Si-rich hard Laves phase, and its wear resistance mainly depends on the proportion of the Laves phase. Therefore, accurately determining the Laves phase ratio is of great significance for material performance evaluation and quality control, and metallography is the main method to achieve this.
[0038] Currently, commonly used metallographic etching methods for cobalt-based alloys have the following main shortcomings:
[0039] Aqua regia etching method: Aqua regia, prepared by mixing hydrochloric acid and nitric acid in a 3:1 ratio, is used to etch the phase for several seconds at room temperature. Although this method can clearly show the interface between the γ matrix and the Laves phase, the color contrast between the two phases under a microscope is generally poor, resulting in low differentiation.
[0040] Murakami reagent etching method: A reagent is prepared by mixing potassium ferricyanide, potassium hydroxide (or sodium hydroxide), and water in a ratio of 10g:10g:100ml, heated to boiling, and then etched for several minutes. This reagent can stain the matrix, causing the Laves phase to appear as white raised areas. However, potassium ferricyanide releases highly toxic hydrogen cyanide gas under certain conditions, and improper disposal of the waste liquid can easily pollute the environment. Therefore, its storage and use in the laboratory are strictly limited, as it is detrimental to operator health and environmental protection.
[0041] Oxalic acid electrolytic etching method: A 10% oxalic acid aqueous solution is used as the electrolyte, and electrolytic etching is performed for several seconds at a voltage of 6~12V. This method can also clearly show the interface between the γ matrix and the Laves phase, but the contrast between the two phases is still insufficient.
[0042] In summary, when using aqua regia etching and oxalic acid electrolytic etching, the matrix phase and Laves phase have insufficient contrast under a metallographic microscope, making it impossible to directly use the grayscale extraction method of metallographic analysis software for effective differentiation and quantitative determination; while the Murakami reagent etching method involves highly toxic chemicals, which greatly limits its application scope.
[0043] This embodiment provides an electrolytic coloring display method for corrosion-resistant cobalt-molybdenum-chromium alloys. An alkaline aqueous solution containing soluble molybdate is used as the electrolytic coloring reagent. The cobalt-molybdenum-chromium alloy sample is used as the anode for electrolytic treatment, so that a molybdenum oxide coloring film is formed on the surface of the Laves phase, thereby making the matrix phase and the Laves phase appear in different colors under a metallographic microscope.
[0044] The basic principle of metallographic coloring is as follows: a thin film of a certain thickness is prepared on the test surface of the sample through techniques such as thermal oxidation, electrolytic anodizing, and specific chemical staining reagents. Utilizing the thin film interference phenomenon, different phases exhibit different colors under an optical microscope. Based on the above principle, this invention selects electrolytic anodizing as the reagent development method, using an alkaline aqueous solution containing soluble molybdate. The Laves phase is rich in Mo and Si, exhibiting high corrosion resistance under alkaline electrolysis conditions, and is used as the driving force for the MoO4 in the microcathode solution. 2- A reduction reaction occurs; while the matrix phase (γ solid solution), acting as the anode, dissolves, resulting in enhanced surface reflection and a bright white appearance. The reaction formula is as follows:
[0045] Anodic reaction (γ solid solution): Co-2e - =Co 2+ Cr-2e - =Cr 3+ The base metal (Co, Cr, etc.) loses electrons and becomes ions that enter the solution. The microscopic surface is electrochemically smoothed, resulting in a significant increase in brightness and a bright white color.
[0046] Cathode reaction (Laves phase): MoO4 2- +2H₂O + 2e - =MoO2+4OH - Brown MoO2 is generated and deposited on the surface of the Laves phase;
[0047] As a result, the two phases form a distinct color contrast under a metallographic microscope.
[0048] In this embodiment, the specific steps include:
[0049] (1) Sample preparation: The test surface of the cobalt-molybdenum-chromium alloy sample is successively polished with 80-mesh, 240-mesh, 400-mesh, 800-mesh, and 1200-mesh wet sandpaper, and then polished with a soft cloth and diamond polishing agent with a particle size of 0.5μm until the test surface is free of scratches, contamination, and has a mirror finish; (2) Preparation of electrolytic reagent: Prepare the electrolytic reagent by adding 5g~15g of sodium hydroxide and 5g~10g of sodium molybdate per 100mL of aqueous solution, and stir evenly; (3) Electrolysis Color: Using the prepared cobalt-molybdenum-chromium alloy sample as the anode and stainless steel as the cathode, immerse the sample inspection surface in the electrolytic reagent, keep the sample and stainless steel cathode at a distance of 1cm~5cm, pass DC current to electrolyze under room temperature conditions, control the current to 0.5A~1.5A, adjust the voltage to 3V~10V, and the electrolysis time to 15s~100s; (4) Cleaning: Take out the sample, rinse the inspection surface with deionized water and anhydrous ethanol, and air dry it for metallographic observation.
[0050] It should be noted that in this embodiment, the voltage will automatically vary within a certain range depending on the sample size and reagent concentration, generally controlled between 3V and 10V. During operation, only a constant current needs to be set; the voltage value is automatically determined by the resistance of the electrolysis system, requiring no additional adjustment. Furthermore, the operator can also actively adjust the voltage within the 3V to 10V range as needed to achieve manual control of the coloring effect.
[0051] The following examples and comparative examples all use as-cast Tribaloy T-400 cobalt-molybdenum-chromium alloy as the test object to verify the feasibility of the electrolytic coloring display method described in this invention.
[0052] Example 1
[0053] (1) Sample preparation: The Tribaloy T-400 alloy sample inspection surface was polished with 80 mesh, 240 mesh, 400 mesh, 800 mesh and 1200 mesh water sandpaper, and then polished with a velvet cloth and 0.5μm diamond polishing agent. The sample inspection surface was made to eliminate the influence of the original processing, be free of pollution and have a mirror finish.
[0054] (2) Preparation of electrolytic reagent: Add 10g of sodium hydroxide to 100mL of aqueous solution according to volume ratio, stir evenly, then add 8g of sodium molybdate, stir evenly again, and let stand for 1min.
[0055] (3) Electrolytic coloring: Connect a DC power supply, use the prepared Tribaloy T-400 sample as the anode and stainless steel as the cathode, immerse the polished surface in the above electrolytic reagent, keep the sample 3 cm away from the stainless steel cathode, carry out electrolysis at room temperature, control the current to 0.8 A, and keep it for 30 s.
[0056] (4) Cleaning: Take out the sample and immediately rinse the test surface with deionized water and anhydrous ethanol. Let the surface air dry and prepare for observation with a metallographic microscope.
[0057] Observation results: such as Figure 1 As shown, the Laves phase is brown and the matrix phase is bright white. The two phases are clearly distinguishable, and the proportion of the Laves phase can be automatically determined directly using the grayscale method of metallographic image analysis software.
[0058] Comparative Example 1
[0059] (1) Sample preparation: Same as step (1) in Example 1.
[0060] (2) Preparation of electrolytic reagent: Add 10g of sodium hydroxide to 100mL of aqueous solution according to the volume fraction, stir evenly, and let stand for 1min.
[0061] (3) Electrolytic coloring: Connect a DC power supply, use the prepared Tribaloy T-400 sample as the anode and stainless steel as the cathode, immerse the polished surface in the above electrolytic reagent, keep the sample 3 cm away from the stainless steel cathode, carry out electrolysis at room temperature, control the current to 0.8 A, and keep for 20 s.
[0062] (4) Cleaning: Take out the sample and immediately rinse the test surface with deionized water and anhydrous ethanol. Let the surface air dry and prepare for observation with a metallographic microscope.
[0063] Observation results: such as Figure 2 As shown, the test surface of the sample is locally corroded, presenting a corrosion artifact, and the true metallographic structure is not visible, indicating that an alkaline solution without sodium molybdate cannot achieve selective coloring of cobalt-molybdenum-chromium alloys.
[0064] Comparative Example 2
[0065] (1) Sample preparation: Same as step (1) in Example 1.
[0066] (2) Preparation of etching agent: Add 20 mL of nitric acid to 60 mL of hydrochloric acid according to the volume ratio to prepare aqua regia, and let stand for 2 min.
[0067] (3) Etching: Immerse the prepared Tribaloy T-400 sample test surface in aqua regia and etch at room temperature for 5 seconds before removing it.
[0068] (4) Cleaning: Take out the sample and immediately rinse the test surface with deionized water and anhydrous ethanol. Let the surface air dry and prepare for observation with a metallographic microscope.
[0069] Observation results: such as Figure 3 As shown, the grain boundaries are clearly visible, but the matrix phase and the Laves phase both exhibit similar colors, with no obvious color contrast between the two phases, making it impossible to automatically determine the proportion of the Laves phase using the grayscale method.
[0070] Comparative Example 3
[0071] (1) Sample preparation: Same as step (1) in Example 1.
[0072] (2) Preparation of electrolytic reagent: Add 10g of oxalic acid to 100mL of aqueous solution according to volume ratio, stir evenly, and let stand for 1min.
[0073] (3) Electrolytic coloring: Connect a DC power supply, use the prepared Tribaloy T-400 sample as the anode and stainless steel as the cathode, immerse the polished surface in the above electrolytic reagent, keep the sample 3 cm away from the stainless steel cathode, carry out electrolysis at room temperature, control the current to 0.5 A, and hold for 10 s.
[0074] (4) Cleaning: Take out the sample and immediately rinse the test surface with deionized water and anhydrous ethanol. Let the surface air dry and prepare for observation with a metallographic microscope.
[0075] Observation results: such as Figure 4 As shown, the grain boundaries are clear, but there is no obvious color contrast between the matrix phase and the Laves phase, making it impossible to automatically determine the proportion of the Laves phase using the grayscale method.
[0076] Comparative Example 4
[0077] (1) Sample preparation: Same as step (1) in Example 1.
[0078] (2) Preparation of etching agent: Add 20 mL of hydrochloric acid to 100 mL of aqueous solution according to volume ratio, add 1 g of sodium metabisulfite, stir evenly, and let stand for 1 min.
[0079] (3) Etching: Immerse the prepared Tribaloy T-400 sample test surface in the above reagent, etch at room temperature for 20 seconds and then take it out.
[0080] (4) Cleaning: Take out the sample and immediately rinse the test surface with deionized water and anhydrous ethanol. Let the surface air dry and prepare for observation with a metallographic microscope.
[0081] Observation results: such as Figure 5 As shown, the test surface of the sample showed no coloring effect, indicating that Beraha reagent is not suitable for metallographic coloring of cobalt-molybdenum-chromium alloys.
[0082] The metallographic observation results of Example 1 and Comparative Examples 1-4 are shown in Table 1 below:
[0083] Table 1. Metallographic observation results of Example 1 and Comparative Examples 1-4
[0084] Electrolytic / Etching Reagent processing method Observation results Example 1 10g NaOH + 8g sodium molybdate + 100mL aqueous solution Electrolysis, 0.8A, 30s The Laves phase is brown, while the matrix phase is bright white, with significant contrast. Comparative Example 1 10g NaOH + 100mL aqueous solution (excluding molybdate) Electrolysis, 0.8A, 20s Localized corrosion, with no visible actual tissue. Comparative Example 2 20mL nitric acid + 60mL hydrochloric acid Etching, 5s The grain boundaries are clear, and there is no obvious color contrast between the two phases. Comparative Example 3 10g oxalic acid + 100mL aqueous solution Electrolysis, 0.5A, 10s The grain boundaries are clear, and there is no obvious color contrast between the two phases. Comparative Example 4 1g sodium metabisulfite + 20mL hydrochloric acid + 100mL aqueous solution Etching, 20s No coloring effect
[0085] As can be seen from Table 1, the Laves phase appears brown and the matrix phase appears bright white only when the electrolytic reagent contains both alkaline substances and soluble molybdate, with a significant contrast between the two phases.
[0086] While the present invention has been disclosed above, it is not limited thereto. Any person skilled in the art can make various modifications and alterations without departing from the spirit and scope of the invention; therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.
Claims
1. A method for electrolytic coloring display of corrosion-resistant cobalt-molybdenum-chromium alloys, characterized in that, An alkaline aqueous solution containing soluble molybdate was used as the electrolytic coloring reagent, and a cobalt-molybdenum-chromium alloy sample was used as the anode for electrolytic treatment to form a molybdenum oxide coloring film on the surface of the Laves phase, so that the matrix phase and the Laves phase exhibit different colors under a metallographic microscope.
2. The electrolytic coloring display method according to claim 1, characterized in that, Includes the following steps: An aqueous solution containing an alkaline substance and a soluble molybdate was prepared as an electrolytic coloring reagent. The prepared cobalt-molybdenum-chromium alloy sample was used as the anode and an inert conductive material as the cathode. The sample was immersed in the electrolytic coloring reagent and electrolytically colored by passing a direct current through it.
3. The electrolytic coloring display method according to claim 2, characterized in that, The electrolytic coloring process makes the Laves phase appear brown and the matrix phase appear bright white, creating a color contrast between the two under a metallographic microscope.
4. The electrolytic coloring display method according to claim 2, characterized in that, The preparation method of the electrolytic coloring reagent is as follows: add 5g~15g of alkaline substance and 5g~10g of soluble molybdate to every 100mL of aqueous solution.
5. The electrolytic coloring display method according to claim 4, characterized in that, The soluble molybdate is one or more of sodium molybdate, potassium molybdate, or ammonium molybdate; the alkaline substance is one or two of sodium hydroxide and potassium hydroxide; and the inert conductive material is one or more of stainless steel, platinum, and graphite.
6. The electrolytic coloring display method according to claim 1, characterized in that, Includes the following steps: (1) Sample preparation: Grind and polish the test surface of the cobalt-molybdenum-chromium alloy sample to a mirror finish; (2) Preparation of electrolytic reagent: Dissolve sodium hydroxide and sodium molybdate in water and stir evenly to obtain the electrolytic coloring reagent; (3) Electrolytic coloring: Using the prepared cobalt-molybdenum-chromium alloy sample as the anode and stainless steel as the cathode, the test surface of the cobalt-molybdenum-chromium alloy sample is immersed in the electrolytic coloring reagent and electrolyzed by passing a direct current through it. (4) Cleaning: Take out the sample, rinse the test surface with deionized water and anhydrous ethanol, and air dry it for metallographic observation.
7. The electrolytic coloring display method according to claim 6, characterized in that, In step (3), the distance between the cobalt-molybdenum-chromium alloy sample and the stainless steel is 1cm to 5cm.
8. The electrolytic coloring display method according to claim 6, characterized in that, In step (3), the electrolysis current is 0.5A~1.5A, the voltage is 3V~10V, and the electrolysis time is 15s~100s.
9. The electrolytic coloring display method according to claim 6, characterized in that, In step (1), 80-grit, 240-grit, 400-grit, 800-grit, and 1200-grit wet sandpaper are used for polishing in sequence, and a soft cloth is used in conjunction with a diamond polishing agent with a particle size of 0.5μm for polishing.
10. The electrolytic coloring display method according to claim 1, characterized in that, The cobalt-molybdenum-chromium alloy sample was Tribaloy T-400.
Citation Information
Patent Citations
An electrolytic etching method for precipitation strengthening phases in cobalt-based alloys
CN109763165B
Corrosive agent for displaying metallographic structure of cobalt chromium molybdenum alloy and corrosion method
CN111424279A